2007
DOI: 10.1682/jrrd.2007.01.0001
|View full text |Cite
|
Sign up to set email alerts
|

Objectively assessing balance deficits after TBI: Role of computerized posturography

Abstract: Abstract-Balance impairment, or postural instability, is a common source of residual physical disability after severe traumatic brain injury (TBI). Standardized functional measures such as the Functional Independence Measure (FIM) do not specifically assess balance. Furthermore, no agreement exists as to the optimal way to objectively measure balance problems in the TBI population. Technological advances have led to force-plate balance measurement known as computerized posturography testing (CPT). Published CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 21 publications
2
44
0
5
Order By: Relevance
“…In this sense, the high number of posturographic studies reported here provides an overview of how ABI patients manage to achieve postural stability after their first attempt to stand unassisted. Our data confirm the deficit of these patients in managing vestibular afferents and the clear dominance of the visual afferents across the process of regaining postural balance [12][13][14]37]. This also suggests that, regardless of the intensity of balance impairment, in these patients there is a common mechanism of sensory processing.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In this sense, the high number of posturographic studies reported here provides an overview of how ABI patients manage to achieve postural stability after their first attempt to stand unassisted. Our data confirm the deficit of these patients in managing vestibular afferents and the clear dominance of the visual afferents across the process of regaining postural balance [12][13][14]37]. This also suggests that, regardless of the intensity of balance impairment, in these patients there is a common mechanism of sensory processing.…”
Section: Discussionsupporting
confidence: 83%
“…The emergence of more technologically advanced systems has corroborated these data and has also demonstrated the patients' overreliance on visual compensatory strategies to maintain their balance [12][13][14]. Additionally, according to these studies, when standing quiet on a posturographic platform, persons with ABI tend to sway more in the sagittal and lateral directions and are slower in weight-shifting than controls.…”
mentioning
confidence: 88%
“…CPT also provides data about the pattern of postural instability, which may be useful in guiding rehabilitation interventions [73]. More traditional quantitative balance tests include variations of the Romberg test [74], the test of sway [75], and the Berg Balance Scale [76].…”
Section: Postural Instability (Balance Problems)mentioning
confidence: 99%
“…In moderate-tosevere TBI, objective impairment of early balance function is ubiquitous, can be measured on routine physical examination, and is predictive of rehabilitation outcome [12][13]. Objective balance impairments persisting months to years after moderate-to-severe TBI have also been documented on computerized posturography testing (CPT), a method of quantifying balance through body weight shifts on a force plate under normal and altered sensory conditions [14]. The Sensory Organization Test (SOT) is a component of CPT that measures information about the integration of the sensory components of standing balance (visual, proprioceptive, and vestibular) and generates an outcome measure called the equilibrium score that assesses the overall coordination of these systems to maintain standing posture [9].…”
Section: Introductionmentioning
confidence: 99%